The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1042/bsr20180876
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin attenuates mitochondrial injury and renal tubular cell apoptosis in experimental contrast-induced acute kidney injury in rats

Abstract: Reactive oxygen species (ROS) overproduction and renal tubular epithelial cell (TEC) apoptosis are key mechanisms of contrast-induced acute kidney injury (CI-AKI). Mitochondria are the main source of intracellular ROS. In the present study, the characteristics of mitophagy and the effects of rapamycin on contrast-induced abnormalities in oxidative stress, mitochondrial injury and mitophagy, TEC apoptosis and renal function were investigated in a CI-AKI rat model. Rats were divided into control group, CI-AKI gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…Rapamycin treatment, as a positive control, also induced a large number of autophagic fluorescent spots. The red fluorescent expression of cells in the positive control group was stronger than that in the GOtreated group, which showed that rapamycin enhanced autophagy [37]. The fluorescence microscopy results further confirmed that GO triggered autophagy in F98 cells, which was consistent with the TEM results.…”
Section: Autophagy Is Triggered Following Go Exposuresupporting
confidence: 83%
“…Rapamycin treatment, as a positive control, also induced a large number of autophagic fluorescent spots. The red fluorescent expression of cells in the positive control group was stronger than that in the GOtreated group, which showed that rapamycin enhanced autophagy [37]. The fluorescence microscopy results further confirmed that GO triggered autophagy in F98 cells, which was consistent with the TEM results.…”
Section: Autophagy Is Triggered Following Go Exposuresupporting
confidence: 83%
“…Mitophagy plays an important role in the clearance of damaged mitochondria (Linkermann et al, 2014). The reduction of mitophagy significantly exacerbated cell apoptosis and tissue damage of AKI (Zhao et al, 2017;Tang et al, 2018;Yang et al, 2018). In the present study, activation of mitophagy was found in HK-2 cells after I/R treatment.…”
Section: Discussionsupporting
confidence: 55%
“…Rapamycin treatment, as a positive control, also induced a large number of autophagic fluorescent spots. The red fluorescent expression of cells in the positive control group was stronger than that in the GO-treated group, which showed that rapamycin enhanced autophagy [37]. The fluorescence microscopy results further confirmed that GO triggered autophagy in F98 cells, which was consistent with the TEM results.…”
Section: Autophagy Is Triggered Following Go Exposuresupporting
confidence: 82%